'Tired, afraid, breathless … .' An international survey of the exercise experience for people living with pulmonary hypertension. (November 2020) - Chia, Karen S.W.; Brown, Karen; Kotlyar, Eugene; Wong, Peter K. K.; Faux, Steven G.; Shiner, Christine T.
Patients with pulmonary hypertension are more sedentary than the general population, but attitudes and experiences that may influence their exercise behaviour remain poorly understood. This study identified patterns of behaviour, attitudes towards exercise, barriers and enablers of exercise for people living with pulmonary hypertension. Accessibility of rehabilitation services from a patient perspective was also explored. A voluntary, international survey of people living with pulmonary hypertension was conducted, with mixed quantitative and qualitative data collection. Data from 187 participants in 19 countries were included in the analyses. In total, 52% (95/183) of people with pulmonary hypertension reported that they attempted to engage in regular physical activity. This was less than the proportion who did so prior to diagnosis (61%, 112/184, p = 0.006) and was accompanied by uncertainty and anxiety about exercise. In total, 63% (113/180) of the cohort reported experiencing previous adverse events while exercising, which was associated with a greater likelihood of ongoing exercise concerns and anxiety. Fear, frustration and uncertainty about exercise were noted as common barriers to engaging in exercise with pulmonary hypertension. Other barriers to exercise included intrinsic factors such as debilitating breathlessness and fatigue, and external factors such as cost and access to appropriate services. Most respondents (76%, 128/169) did not have access to a multi-disciplinary rehabilitation service, although an overwhelming majority (92%, 159/172) reported that this would be helpful. Respondents rated education; a supervised, structured exercise programme; and psychology input as the most important components of a multi-disciplinary rehabilitation service for pulmonary hypertension. Health professionals must work together with consumers to co-design rehabilitation services that will facilitate exercise and increased activity for people living with pulmonary hypertension.